Cruise Ship Tourism 2017
DOI: 10.1079/9781780646084.0304
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and constraints of cruising for the US and Chinese markets.

Abstract: This chapter provides not only an explanation of the underlying motives and constraints of both US and Chinese cruisers, but also relevant information for the cruise industry to make decisions on how to create products/services and marketing materials to better retain current cruisers and to entice non-cruisers to take their first cruise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Hence, there is a need to determine the motivational factors influencing a passenger's choice to cruise and how these factors intersect with cruise itinerary (cruise venue) and cruise experience (if they are first-time passengers or repeat cruisers). Despite the recent research in this industry, some severe gaps in the literature persist (Petrick et al, 2017;Zou et al, 2017;Hung, 2018;Han & Hyun, 2019). Hung and Petrick (2011) claimed that motivations for luxury cruise travel had been undermined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, there is a need to determine the motivational factors influencing a passenger's choice to cruise and how these factors intersect with cruise itinerary (cruise venue) and cruise experience (if they are first-time passengers or repeat cruisers). Despite the recent research in this industry, some severe gaps in the literature persist (Petrick et al, 2017;Zou et al, 2017;Hung, 2018;Han & Hyun, 2019). Hung and Petrick (2011) claimed that motivations for luxury cruise travel had been undermined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The vast majority of cruising customer research has focused on Western travelers, with studies on cruise tourists from mainland China being comparatively limited (Hung et al, 2018). The emergence of Chinese markets has led to recent research on Chinese travelers' motivations (Hsu and Li, 2017;Petrick et al, 2017), servicescape (Lyu, Hu, & Mao, 2017), and cruising experience (Hung, 2018). These studies, summarized below, reveal that the Chinese market is likely distinct from its Western counterpart.…”
Section: Cruise Tourismmentioning
confidence: 99%
“…Chen, Neuts, Nijkamp, and Liu () revealed that Taiwanese cruisers valued escape, learning, and social bonding more than their Chinese, Hong Kong, and Japanese counterparts, whereas the Japanese were highest on self‐esteem enhancement and lowest on social bonding. For Chinese cruisers, novelty, relaxation, and ocean scenery have been identified as major motivations (Petrick, Zou, & Hung, ; Zou, Migacz, & Petrick, ). Guo and Zhou (), additionally, identified strong beliefs that ocean cruising can demonstrate social status and attract respect from friends and relatives, thus contending that “showing off” is more important than engagement in leisure for its own sake.…”
Section: Literature Reviewmentioning
confidence: 99%